What accounts for China's trade balance dynamics? - Yin Zhang; Guanghua Wan (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2004)
This paper proposes a structural VAR model which extends the frameworks of Hoffmaister and Roldós (2001) and Prasad (1999). The model is then used to analyse the sources of China's trade balance fluctuations in the period of 1985–2000. Efforts are made to distinguish the forces which underlie the long-run trend in trade balance from those with transitory impacts. The effects of four types of shock are examined—the foreign supply shock, the domestic supply shock, the relative demand shock, and the nominal shock. Among other findings, two emerge as important. First, the movements in China's trade are largely the result of real shocks. Second, the Renminbi is undervalued, yet changes in the exchange rate bear little on the trade balance. Therefore, monetary measures would not suffice to redress China's trade `imbalance'. – China ; trade balance ; real exchange rate ; structural VAR ; Law of One Price
Keywords: O53; F40; E0; 330; Handelsbilanz; Monetäre Außenwirtschaftstheorie; China